TANÉAN LANJHÂNG: A Reflection of Guyub and Strengthening of Ukhuwah Among Madurese Society - Raudlatul Jannah; Agik Nur Efendi; Fithriyah Rahmawati (Islamuna: Jurnal Studi Islam, 2021)
The Madurese tribe has unique, distinctive, and remarkable cultures. It is inseparable from a heterogeneous socio-cultural society. Science, morals, ethics, morals, philosophy of life, social interactions correlate with culture. One of the philosophies in Madurese society that is synergized with livelihoods and kinship values ​​is tanean lanjhang. Tanean lanjhang is a residential space pattern within the Madurese community. The settlement consists of ​​a house yard, kobhung, kitchen, stable, well, and several houses. About 2-10 houses are lined up from west to east and inhabited by people with sibling relationships. As a society that upholds religious values, the concept of tanean lanjhang has a very noble, philosophical meaning and is full of Islamic values either deliberately built or ​​arising from the idea of social interaction in tanean lanjhang. This study aims to describe the philosophical meaning of the tanean lanjhang. This current study used a qualitative- descriptive approach and carried out literature review, observation, and interviews to collect the data. The results showed that tanean lanjhang is a sub-structure of unique community settlement layout and has a noble value from the concept of spatial planning or social interaction, which is manifested in several commendable morals, namely strengthening ukhuwah, caring and respecting people, and cooperation. ABSTRAK Suku Madura memiliki berbagai budaya yang unik, khas, bahkan istimewa. Ilmu pengetahuan, akhlak, etika, moral, falsafah hidup, interaksi sosial sesungguhnya berkorelasi dengan budaya. Salah satu falsafah dalam masyarakat Madura yang bersinergi dengan mata pencaharian dan nilai kekerabatan adalah tanean lanjhang. Tanean lanjhang merupakan konstruksi tata ruang pemukiman yang ada di masyarakat Madura. Pemukiman tersebut terdiri dari sebuah area halaman rumah, kobhung, dapur, kandang, sumur dan rumah rumah yang berjejer dari barat ke timur dengan jumlah 2-10 rumah yang dihuni oleh orang orang dengan hubungan saudara kandung. Sebagai masyarakat yang menjunjung nilai religius, maka konsep dari tanean lanjhang memiliki makna yang sangat luhur, filosofis, dan sarat dengan nilai- nilai keislaman, baik nilai yang sengaja dibangun atau nilai yang timbul dari konsep atau interaksi sosial dalam tanean lanjhang. Penelitian ini bertujuan untuk mendeskripsikan makna filosofis yang ada dalam konsep tanean lanjhang. Penelitian ini menggunakan pendekatan deskriptif kualitatif dan teknik Pustaka review, observasi dan wawancara.Hasil penelitian menunjukkan bahwa tanean lanjhangselain sebagai subuah konstruksi tata ruang pemukiman masyarakat yang unik juga memiliki nilai nilai luhur dari konsep tata ruang atau interaksi sosial yang menjadi cerminan konsep kekerabatan masyarakat Madura yang sangat kuat. Sehingga pada akhirnya mampu memperkuat ukhuwah dan memupuk sikap-sikap terpuji seperti sikap peduli, saling menghormati, dan gotong royong.